2015
DOI: 10.12963/csd.15235
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Language Complaints: Are They Reflected in Objective Language Test Performance?

Abstract: Objectives: Subjective language complaints (SLCs) are frequently reported among the elderly. However, SLCs and their relationship with various language functions have not been extensively investigated. The purpose of this study was two-fold: to explore whether SLCs can be related to performance in various objective language tests and to determine which demographic variables are associated with SLCs. Methods: This study gathered responses from 376 elderly participants (mean age, 74.21 ± 6.56 years) to two quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
2
4
0
3
Order By: Relevance
“…These results suggest that CN are highly sensitive to wordfinding changes, possibly due to the frequent use of language in daily life and the potential impacts of word-finding problems on social life. They are consistent with previous studies showing the elevated prevalence of such complaints [8][9][10] . The current study adds to this literature by directly comparing word-finding complaints with complaints from other cognitive domains, therefore providing a complete profile of cognitive complaints in CN.…”
Section: Word Finding Complaints Are Amongst the Most Frequent And Severe In Cnsupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggest that CN are highly sensitive to wordfinding changes, possibly due to the frequent use of language in daily life and the potential impacts of word-finding problems on social life. They are consistent with previous studies showing the elevated prevalence of such complaints [8][9][10] . The current study adds to this literature by directly comparing word-finding complaints with complaints from other cognitive domains, therefore providing a complete profile of cognitive complaints in CN.…”
Section: Word Finding Complaints Are Amongst the Most Frequent And Severe In Cnsupporting
confidence: 93%
“…Apart from memory deficits, a decline related to language performance, and most specifically word-finding difficulties, is also considered to be a very early sign of AD [5][6][7] . Several studies have shown that language and more specifically word-finding complaints are among the most frequent complaints in cognitively normal older adults [8][9][10] . In daily life, these word-finding complaints can manifest in different ways, such as forgetting the names of objects or people and having difficulties finding words in conversations.…”
Section: Introductionmentioning
confidence: 99%
“…They are consistent with previous studies showing the elevated prevalence of such complaints. [8][9][10] The current study adds to this literature by directly comparing word-finding complaints with complaints from other cognitive domains, therefore providing a complete profile of cognitive complaints in CN. Finally, word-finding complaints were significantly more severe than other types of language complaints, which highlight the importance of investigating word-finding complaints in isolation in CN.…”
Section: Word-finding Complaints Are Among the Most Frequent And Seve...mentioning
confidence: 99%
“…에서 전략적으로 정보를 탐색하고 인출하는 능력을 평가하며 (Kempler et al, 1998), 초기의 알츠하이머형 치매 환자나 경도 인지장애 환자를 일반 노인과 구분해 주는 민감한 과제로 알려 져 있다 (Choi, 2008;Cooper et al, 2004) (Amariglio et al, 2011;Kim et al, 2015;Lee et al, 2011;Yim et al, 2017;Youn et al, 2009), 주관적 기억력과 객관적 기억력 사이에는 유의한 상관 이 없다는 연구 결과도 있다 (Derouesné et al, 1999;Jorm et al, 2001;McGlone et al, 1990;Sunderland et al, 1986). (Diaz et al, 2004;Henry & Crawford, 2004;Troyer et al, 1997)…”
Section: 다음으로 생성이름대기 과제는 저장된 어휘집과 의미기억unclassified